Implementasi Peraturan Gubernur Nomor 3 Tahun 2021 Tentang Tambahan Penghasilan Pegawai Dalam Meningkatkan Kinerja dan Disiplin Pegawai Pada Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara - Sri Hastuti; Hamdani Harahap; Budi Hartono (Mahesa Research Center, 2022)
The purpose of this study is to analyze the implementation and obstacles of the Governor's Regulation Number 3 of 2021 concerning Additional Employee Income in Improving Employee Performance and Discipline at the Industry and Trade Office of North Sumatra Province. Descriptive method is used by using a qualitative approach. How to collect data related to the problem under study so that it can be explained descriptively. Data analysis is a process of systematically finding and compiling data obtained from interviews and field observations. The results of the study show that the implementation is still less than optimal, such as: Communication not all the information needed is conveyed and some employees have a poor level of understanding; Resources are still not maximized starting from internet facilities and applications used by employees; Disposition Honesty of employees is not optimal because the data with reality do not match; The structure of the Bureaucratic Coordination has not been maximized because the employees have their respective activities. The inhibiting factors are that employees are considered less informative, internet connections are slow and the applications used often experience interference, the honesty level of some employees is not good, the busyness of each employee causes coordination to take longer.